1998
DOI: 10.2343/geochemj.32.231
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of ilmenite from the Asama ultramafic-mafic layered igneous complex, Mikabu greenstone belt, Sambagawa metamorphic terrane, central Japan.

Abstract: Ilmenite occurs as an intercumulus phase in most gabbroic rocks and some plagioclase wehrlites of the Asama igneous complex, an ultramafic-mafic layered intrusion in the Mikabu greenstone belt, central Japan. The Mg/(Mg + Fee+) ratio of ilmenite reaches 0.35, but generally ranges from 0.01 to 0.22; the Fe3+ content varies from 0.04 to 0.26 pfu (per formula unit calculated on the basis of 0 = 3). Ilmenite crystallized together with intercumulus clinopyroxene in plagioclase wehrlite, but most of the calculated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The magma crystallizing the Kanakasu xenocrystic chromite was apparently different from island-arc or mid-oceanic ridge alkalic basalts, and similar to Hawaiian alkalic basalts. Hawaiian basalt-like rocks have been reported in greenstone bodies of some other geological terranes in Japan (Arai, 1992;Agata, 1994Agata, , 1998. The palaeomagnetism of greenstones in the Mino terrane has been investigated by Hattori and Hirooka (1979), who have shown that these greenstones exhibit geomagnetic inclinations around 08; their igneous activity probably took place in an equatorial area.…”
Section: Discussionmentioning
confidence: 99%
“…The magma crystallizing the Kanakasu xenocrystic chromite was apparently different from island-arc or mid-oceanic ridge alkalic basalts, and similar to Hawaiian alkalic basalts. Hawaiian basalt-like rocks have been reported in greenstone bodies of some other geological terranes in Japan (Arai, 1992;Agata, 1994Agata, , 1998. The palaeomagnetism of greenstones in the Mino terrane has been investigated by Hattori and Hirooka (1979), who have shown that these greenstones exhibit geomagnetic inclinations around 08; their igneous activity probably took place in an equatorial area.…”
Section: Discussionmentioning
confidence: 99%
“…The mountain consists of the Asama igneous body, which is intruded into Jurassic Mikabu greenstones that were metamorphosed to low grades during the high-P/T Sanbagawa metamorphism. As reported by Nakamura (1971) and Agata (1998), the igneous complex consists of a layered sequence of mafic and ultramafic rocks that are lithologically divided into three zones. The lowermost zone consists of peridotites, the middle zone of alternating gabbros and peridotites, and the upper zone of gabbroic rocks (Fig.…”
Section: Asama Mountain (Asamagatake) In Toba Citymentioning
confidence: 99%
“…7 Geo logy of Mt. Asama area, illustrating the structural layering of the igneous complex and the main faults (after Agata, 1998). The photo on the right, taken from the mountaintop observatory,demonstrates how the inferred MTL trace (dotted line) and related lineaments continue to the northeast fro m the Kii Peninsula (Futami area) to the Chubu Region in Japan.…”
Section: Asama Mountain (Asamagatake) In Toba Citymentioning
confidence: 99%